Ginkgo biloba extract suppresses hepatocellular carcinoma progression by inhibiting the recruitment of myeloid-derived suppressor cells through reduced CXCL1 secretion via SRC downregulation - Xu, Zhiliang; Liang, Siqin; You, Xiaoxiang; Jin, Anan; Mao, Lei; Zhong, Fangyan; Yuan, Tinghao; He, Jun; Yi, Bo; Li, Ming; Tu, Qiang (Frontiers in Immunology, 2026)
BackgroundHepatocellular carcinoma (HCC) remains one of the leading causes of cancer-related mortality worldwide, characterized by poor prognosis and limited therapeutic efficacy. Ginkgo biloba extract (GBE) has demonstrated antitumor potential, yet its precise molecular mechanisms in HCC are not fully understood.PurposeThis study aimed to elucidate how GBE suppresses HCC progression and to explore its underlying molecular mechanisms.MethodsA subcutaneous HCC mouse model was established to evaluate the antitumor effects of GBE in vivo. Network pharmacology, molecular docking, and in vitro assays were integrated to identify and validate the core molecular targets of GBE.ResultsGBE treatment significantly inhibited tumor growth and reduced myeloid-derived suppressor cells (MDSCs) recruitment within the tumor microenvironment. Network pharmacology identified proto-oncogene tyrosine-protein kinase (SRC) as a key target of GBE. Molecular docking revealed strong spontaneous binding affinity between active GBE components and SRC. In vitro experiments confirmed that GBE markedly downregulated SRC expression and CXCL1 secretion in HCC cells, whereas SRC overexpression reversed these effects. Clinical data further showed that SRC was upregulated in HCC tissues and correlated with poor prognosis and elevated MDSCs infiltration.ConclusionGBE suppresses HCC progression by downregulating SRC expression, which consequently reduces CXCL1 secretion and limits MDSCs recruitment within the tumor. These findings highlight GBE as a promising adjuvant immunotherapeutic strategy for HCC.